ISPC Commentary on the Revised Proposal for CRP3.6 - September 2012 - CGIAR Independent Science and Partnership Council (CGIAR Independent Science and Partnership Council, 2012)
ISPC Commentary on the revised proposal for CRP 3.6: Dryland cereals (Revision of August 2012).